Variability in tannins and protein content and physical properties in faba bean grains (Vicia faba L.) (Bioagro, 2020)
Faba bean (Vicia faba L.) is a plant with important protein content (14-35%) and responds to the basic needs of farmers who favor the conservation of traditional local cultivars. Its nutritional value is compromised by the presence of tannins that decrease the use of proteins and darkens the grain. The objective of this work was to identify variability in tannin content, protein and physical properties in grains of 36 broad bean cultivars, evaluated in field, in Metepec, Mexico. Variability was found in each of the evaluated variables. The cultivars ST21, M29 and M30 showed the greatest differences in content of condensed and hydrolyzable tanins, protein and physical properties. The color of the testa shows the variability of the materials. All cultivars, except M30, have large grains. Regarding grain hardness, ST21 with 21.23 N was the softest cultivar. Protein content was highest in cultivar C17 (30.10 %), and lowest in ST21 (14.17%), followed by Z28 (17.07 %). Four groups with leucocyanidin equivalents per gram were formed, with several cultivars above a value of 4.0, and where ST21 with 2.30 was the lowest. For methyl gallate equivalents, A4 with a value of 15.43 was the highest, and ST21 with 6.07 the lowest. The cultivars C17, M32, A8 and A3 are the most representative in terms of high protein content and lower content of condensed tannins.
Keywords: Color; cultivar variability; grain hardness; local cultivars